Case report: A clinical case study of six patients with Chlamydia psittaci pneumonia - Dai, Jinmeng; Lian, Xue; Mo, Juanfen; Li, Xiaosi; Mo, Weiqiang; Wang, Haiqin; Jiang, Jianping (Frontiers in Cellular and Infection Microbiology, 2023)
Objective To investigate the clinical features, diagnosis, and treatment of Chlamydia psittaci (C. psittaci) pneumonia. Methods We retrospectively analyzed the clinical data of six patients with C. psittaci pneumonia who were admitted to the Division of Pulmonary and Critical Care Medicine of the Second Hospital of Jiaxing from December 2021 to September 2022. Results All patients reported a fever and other accompanying symptoms, including cough (5/6), chest tightness (1/6), fatigue (2/6), and headache (1/6). Laboratory results showed that all patients had high levels of C-reactive protein (CRP≥70 mg/L), procalcitonin (PCT; 2 patients with PCT levels ≥0.5 ng/L), and erythrocyte sedimentation rate (ESR). Lactate dehydrogenase (LDH) and aspartate aminotransferase (AST) levels were elevated in 3/6 and of 2/6 patients, respectively. Chest computed tomography (CT) of most patients showed patchy, high-density shadows with partial consolidation, accompanied by air bronchogram signs and pleural effusion. Six patients were diagnosed with C. psittaci pneumonia using metagenomic next-generation sequencing (mNGS). They showed favorable outcomes following immediate adjustment of the regimen to doxycycline-based therapy and hydration, nutrition, and other follow-up treatments. In the imaging findings obtained at one-two month, the lesions were completely cleared, suggesting a favorable prognosis. Conclusion Patients with C. psittaci pneumonia commonly present sepsis and rapidly progressing disease. Early diagnosis is critical for C. psittaci pneumonia using mNGS, which can lead to favorable prognoses via immediate adjustment therapies.